Mobility, work and citizenship in uncertain times: An ethnography of cross-border links at the boundaries of the European Union - Ignacy Jóźwiak (University of Warsaw, Centre of Migration Research (CMR), 2016)
This paper explores the role of the state border in the daily life of the borderlanders, the inhabitants of the Transcarpathia region in Western Ukraine. Based on ethnographic fieldwork in the two border locations, it offers an insight into the region which has been affected by the 'EUropeanization' (due to its geographical location and historical legacies) of the border regime on the one hand and, as entire country, by the post 2014 crisis in Ukraine. The study points to the practices of the use of the border and cross-border links as well as the changes the patterns for doing so have undergone. In the face of political crisis and economic recession, Ukrainians face greater pressure to migrate while in the country's Western borderlands an increased utilization of already existing cross-border links can be observed. The subject-matter is set it in the framework of transnationalism and borderlands studies.
Keywords: 330; state border; borderlands; migration; ethnography; transnationalism